Experimental studies of base pressure regulation via tiny jets at high inertia levels - Khan, Ambareen; Khan, Sher Afghan (MedCrave Group, 2026)
The current investigation presents results from an effort to control the base pressure in the flow-separated area. The investigation intends to estimate the efficiency of the stream controllers in regulating the base pressure pipes. Microscopic jets of 0.5 mm in radius are sited at a gap of 900 at 13 mm starting from the principal axis of the central jet. The inertia levels considered in the present study are M = 1.8, 2.0, 2.5, and 3.0. Axi-symmetric circular pipes were used with the nozzles, and D2/D1 1.6 to 2.5. The L/D ratio was varied from unity to 10, and the level of expansion from 3 to 11. The base pressure depends on the NPR and the speed. When deciding on pressure in the recirculation area, the level of expansion plays a significant role in determining its size. Also, when the jet was released into the pipes with a fixed relief to the flow, the flow attached to the duct for all Mach numbers, and the NPRs were tested. Furthermore, the expansion level significantly affects the base pressure & the controller’s capability